Respon Pertumbuhan Tanaman Tanaman Cabai Keriting (Capsicum annuum L.) Terhadap Penambahan Limbah Air Detergent dan Limbah Cair Ampas Tahu - Thalia Amara Hidayat Putri; Hayatul Rahmi; Rika Yayu Agustini (Jurnal Ilmiah Wahana Pendidikan, 2021)
Curly chili (Capsicum annuum L.) is included in the horticultural plant group of fruit vegetables that have high economic value. The development of curly chili aims to increase the productivity of chili plants. One of the efforts to increase the production of chili plants by cultivating the land properly so that soil fertility is maintained, one of them is with proper fertilization. The purpose of this study was to determine the response of growth of curly chili plants to the addition of detergent water waste and tofu waste liquid waste. The research was carried out from February 2021 to June 2021, in Sukaluyu Village, Telukjambe Timur District, Karawang. The research method used is factorial randomized block design (RAK), the first factor is detergent water waste (P) consisting of 3 levels: P0 (0%), P1 (25%), P2 (50%) and the second factor is tofu waste liquid waste. (A) consists of 3 levels: A0 (0%), A1 (10%), A2 (20%). There were 9 treatments with 3 replications so there were 27 experimental units. The results showed that there was no interaction between the addition of detergent water waste and tofus waste liquid waste on the growth of curly chili (Capsicum annuum L.). In addition, there was no concentration of detergent water waste and tofu waste liquid waste which gave optimal results on the growth of curly chili (Capsicum annuum L.).